The impact of transient heat flux on tungsten fiber-reinforced tungsten materials - Tianyu, Zhao; Shaoqiang, Xu; Juan, Du; Pan, Wen; Fan, Feng; Jialin, Li; Jun, Tang; Fanya, Jin; Kejia, Zhang (Fusion engineering and design, 2026)
•The stability of tungsten fibers and interfaces in Wf/Wm was evaluated for the first time using an electron beam device.•In the experiment, the deflection of transient thermal shock cracks caused by interfacial debonding was observed for the first time, which confirms the special role of the fiber-interface-matrix energy dissipation structure under high thermal flux.•Under transient thermal shock, although Wf/Wm exhibit a higher cracking threshold, their cracking behavior is similar to that of ITER-W. Tungsten fiber-reinforced tungsten materials (Wf/Wm), as an emerging plasma-facing material, hold promise in addressing the brittleness issues associated with traditional tungsten materials. However, the impact of transient thermal loads in nuclear fusion reactors, particularly on the tungsten fibers and interfacial structures, has been less studied, which hampers the further application and development of these materials. This paper simulates Edge Localized Modes (ELMs) events using an EMS-60 electron beam facility to subject Wf/Wm to transient thermal shock and compares the changes in fibers and interfaces before and after the transient thermal shock. The following conclusions are drawn: (1) Compared to pure tungsten materials,Wf/Wm exhibit superior performance under transient thermal loads. (2) Although in this study, the tungsten fibers and interfaces, when directly exposed to high thermal loads, can still effectively prevent crack propagation, they both experience significant performance degradation and loss of integrity. We infer that if the number of thermal shock cycles is further increased, the likelihood of failure of the fibers and interfaces may be significantly enhanced. Therefore, special attention should be paid to the failure of Wf/Wm caused by plasma flux in practical applications. (3) Tungsten fibers have an excellent inhibitory effect on cracks along the heat flux direction, and their ideal arrangement is beneath the material surface, at a position hundreds of micrometers away from the surface, where the fibers and interfacial structures can be preserved intact, effectively impeding crack propagation.